Cost-Effectiveness of Administering Rituximab for Steroid-Dependent Nephrotic Syndrome and Frequently Relapsing Nephrotic Syndrome: A Preliminary Study in Japan - Takura, Tomoyuki (Sci Rep, 2017)
With regard to the use of rituximab for patients with steroid-dependent nephrotic syndrome and frequently relapsing nephrotic syndrome, not only has the regimen not been clinically verified but also there is a lack of health economics evidence. Therefore, we conducted a prospective clinical study on 30 patients before (with steroids and immunosuppressants) and after introducing rituximab therapy. Relapse rates and total invoiced medical expenses were selected as the primary endpoints for treatment effectiveness and treatment costs, respectively. As secondary endpoints, cost-effectiveness was compared before and after administering rituximab in relation to previous pharmacotherapy. The observation period was 24 months before and after the initiation of rituximab. We showed that there was a statistically significant improvement in the relapse rate from a mean of 4.30 events before administration to a mean of 0.27 events after administration and that there was a significantly better prognosis in the cumulative avoidance of relapse rate by Kaplan–Meier analysis (p < 0.01). Finally, the total medical costs decreased from 2,923 USD to 1,280 USD per month, and the pre–post cost-effectiveness was confirmed as dominant. We, therefore, conclude that treatment with rituximab was possibly superior to previous pharmacological treatments from a health economics perspective.